A (In)visibilidade dos Kotirias: a sobrevida pela tradução - Rezende, Patrick (Tusaaji: A Translation Review, 2016)
From a postcolonial and poststructuralist perspective, this article reflects on how history is continuously retold within a process that (de)limits the identity characteristics of minority cultural groups, within the walls of a “dominating” world. Indigenous peoples in the Americas have had their (hi)stories silenced by the will of the “Western” world, a will that more recently has been bending, fortunately, towards m’ypé, that is, attempts at “mending”. Taking m’ypé into consideration, translation can be rethought as a way of giving visibility to groups that find, in their narrative forms, ways of (re)telling their (hi)stories. In this article I examine a narrative from the Kotiria, an indigenous group that lives on the border between Brazil and Colombia. Looking at one narrative—taken from the Série Kotiria, organized by the anthropologist Janet Chernela—and focusing on Lawrence Venuti’s (in)visibility theory, I discuss how we may learn more from the Kotiria’s voices about the indigenous past, and how those voices still address, and directly so, much about the present.